Time between failure of water pipeline in Głubczyce as an element of safe operation of the water supply system - Zimoch, Izabela; Grabuńczyk, Marcin (Instal, 2021)
Management of delivering water intendent for human consumption is essential element of the functioning of the municipality as an independent territorial unit, being at the same time its own task, which in the discussed case is carried out by the water supply company. The collective water supply system, according to the Act on crisis management, belongs to the belong to the country's critical infrastructure. The most important element of the water supply system is the water pipe network, which is crucial point of the completely critical infrastructure. A necessary condition for supplying drinking water to consumers, in accordance with Polish law requirements, is maintaining the efficiency and proper operation of the water pipe network together with the accompanying infrastructure, and the water pipe network must operate reliably both at minimum consumption and during periods of increased water demand. Properly, failure-free functioning of water pipelines is a key element of building a health safety system for residents. The article presents an analysis of operating times (time between failure and downtime) of the water supply network in the municipality of Glubczyce in the aspect of security of critical infrastructure functioning.
Keywords: water pipe network; critical infrastructure; reliability; failure; time between failure; downtime